Techno-Economic Solution For Extending Ccus Application In Natural Gas Fields: A Case Study Of B Gas Field In Indonesia - Prasandi Abdul Aziz; Mohammad Rachmat; Steven Chandra; Wijoyo Niti Daton; Brian Tony (Scientific Contributions Oil and Gas, 2023)
The application of carbon trading has been applied since 2005 in Northern America, has been adapted in Indonesia with pilot scale implementation namely as Carbon Capture and Storage. One of the biggest issue is the lack of financial incentive in conducting the CCS. Therefore, Carbon Capture, Utilization and Storage (CCUS) serves as an alternative to increase the economic value of the injected CO2. This study presents a new approach of CCUS studied in B Field in Indonesia, a natural gas producer with high CO2 and H2S content. By injecting CO2 as a mean of pressure maintenance, 5.8% of incremental gas production is achieved whilst being able to sequester 2.7 million tonnes of CO2 for 10 years operation. This study should become a pioneer in continuing researches related to enhanced CCS methods by increasing the value of CO2 as well as reducing dependency in expensive chemical EOR injection in the future